Manusia dan Moralitas di Tengah Kemajuan Zaman: Tinjauan Filosofis dalam Perspektif Etika Islam Kontemporer - Farkhan Syahrul Mubarok; Khobir, Abdul; Azzuhri, Muhandis (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2026)
The development of modern technology has brought major changes in human life, not only in practical aspects such as communication and access to information, but also affecting the moral and spiritual dimensions of humans. Fast-paced modernity encourages a culture of instant gratification, efficiency, and dependence on digital systems, thus triggering ethical problems such as individualism, the spread of hoaxes, the collapse of privacy, and the weakening of empathy. From a philosophical perspective, this phenomenon is understood through Heidegger's concept of das Gestell, a technological way of thinking that reduces humans to objects, and Zygmunt Bauman's view of liquid modernity, a social era that is fluid and lacks moral certainty. In the context of Islamic ethics, technological advances demand a reaffirmation of moral and spiritual values ​​as the foundation of morality. This research employs a library research method with a descriptive-analytical and philosophical approach to examine the dynamics of human moral change and the relevance of contemporary Islamic ethics in responding to this crisis. Research sources include classical and modern literature, as well as normative texts from the Qur'an and Hadith. The study's findings indicate that moral decline in the digital age is related to technological, socio-cultural, and structural changes in human consciousness. Islamic ethics, through the concepts of insan kamil (the perfect human being), akhlak al-karimah (the noble character), and maqāṣid al-shari'ah (the principles of Islamic law), offers a value framework that balances technological progress with human well-being. This research confirms that revitalizing Islamic ethics can be a crucial solution for maintaining moral integrity, strengthening responsibility, and guiding technological development so that it remains aligned with humanitarian and spiritual values.